The Brothel as Patrimonial Stigma: Study of the object, subjects and heritage values of “Tres Cabezas” (Chimbote, Peru) 2020 – 2021. An investigation carried out during the 2nd wave of COVID-19. - León Ojeda, Carolina Sthefany (2022)
Sex work in women is obscured by various myths and social stigmas; those who promote a mistaken vision on said subject. Therefore, the way to understand it in our context is as that oldest profession in the world or also considered a social necessity. According to García (1999), cultural heritage expresses the solidarity of those who share a set of goods and practices that identify them, but it is also usually a place of social complicity. Likewise, history has shown us that every port has left memories that accompany and revolve around a brothel, which for this investigation is “Tres Cabezas”. For this reason, Arguedas (1971) was the one who related the utopia regarding prostitution in Chimbote, leaving a mark on literature through the Zorro de Arriba and the Zorro de Abajo. In that sense, if there is a "monument" to fishing and steel replicated throughout the city, in memory of what was the "boom" of Chimbote, ¿why not have a monument to the sex trade?, breaking the stigma socio-patrimonial of not disclosing this social meeting center, and turning it into an "emblematic place of debauchery", a witness of social liberation.